AN OPTIMAL TUNING OF INTEGRAL CONTROLLER FOR HYBRID LFC SYSTEM INTEGRATED WITH WIND ENERGY RESOURCES - S.Anbarasi, S.Ramesh, S.Muralidharan (International Journal of Advanced Science and Technology, 2020)
An optimal tuning of Integral controller for Load Frequency Control (LFC) of a multi-area multi-source system using Bacterial Foraging Optimization Algorithms (BFOA) is presented in this paper. The multi-source system considering in this paper consists of thermal power source, hydro power source, gas power resource as well as  a renewable wind power generation sources. The conventional Integral Absolute Error (IAE) is used as an objective function for optimization approaches. To demonstrate the transient performance of the system a Step Load Perturbation (SLP) is applied to the system and the frequency deviation is observed by tuning of integral controller with BFOA approach. To enhance the performance further, the proposed approach is analyzed in presence of High Voltage Direct Current (HVDC) link. To ensure the reliability, the results of the proposed BFOA tuned integral controller are compared with an uncontrolled LFC system under step load perturbations (SLP). The simulation design and analysis of the test system are done through MATLAB SIMULINK tool and the results are measured through fundamental performance indices such as, maximum peak (MP), steady state error (SSE), settling time (ST) and rise time (RT). All the simulation results clearly reveal that, the proposed BFOA tuned integral controller for a hybrid LFC system has better transient performances under SLP and the performance is improved further in presence of HVDC link during the integration of renewable energy resources